Financial Satisfaction Among Married Women - Tanaka Chimbane; Sonya Lutter; Jeremy B. Yorgason; Erin K Holmes (Journal of Financial Therapy, 2026)
Guided by family systems theory and social exchange theory, this study examines the factors related to financial satisfaction among married women, emphasizing the importance of financial values, honesty, and power dynamics within relationships. Findings indicate that sharing financial values with a partner significantly enhances financial satisfaction, while dishonesty and financial power imbalances negatively relate to it. Additionally, higher income strongly correlates with greater financial satisfaction. By linking financial satisfaction to broader relational and well-being outcomes, this study demonstrates the relevance of these findings for financial therapists seeking to enhance financial and personal well-being. Implementing joint financial planning strategies and tailored financial guidance based on life stages can empower women to achieve long-term financial satisfaction and security.
Keywords: financial counseling; financial empowerment; financial honesty; financial planning; financial power dynamics; financial satisfaction